SELF-CARE AND DIETARY PATTERNS AMONG DIABETES MELLITUS PATIENTS IN RAWALPINDI - Hisam, Aliya; Tariq, Naseer Alam; Hammad, Muhammad; Hassan, Umair; Iram, Sania; Tariq, Ifra; Ali, Sajid (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out the knowledge, attitude and practice among diabetic patients regarding their dietary patterns.Study Design: Descriptive cross-sectional study.Place and Duration of Study: In a tertiary care hospital of Rawalpindi of six month’s duration from August, 2013 till January, 2014.Patients and Methods: A sample size of 131 was calculated using the WHO sample size calculator. Convenience sampling technique was used. Clinically diagnosed diabetes mellitus by a consultant and those who were able to show the diabetes medication were included in the study. Any patient unwilling or failing to show the diabetes medicine was excluded from the study. Data was collected by the researcher using pre-tested mixedquestionnaire. Data was entered into and analyzed using SPSS version 20.Results: A total of 135 patients were enrolled in the study, with a mean age of 55.16 ± 10.47 years. There were 92 (68 %) males and 43 (32%) females. Good knowledge regarding diabetes mellitus was observed in 82 (60.7%) of the participants while 53 (39.3%) were having poor knowledge. Positive attitude was observed in 51 (37.8%) participants while negative attitude in 84 (62.2%). Good practice was observed in only 28 (20.7%) while poorpractice was seen in 107 (79.3%) of the participants.Conclusion: Knowledge regarding self-care was sound among the diabetic patients but there existed a wide gap between knowledge and practice. Attitude was positive in the educated class but deficient in the illiterates. Healthy Dietary patterns were satisfactory among the study participants.